Effects of petroleum extraction on Norwegian economy - Malkovský, Michal (2015)
Norway serves as a unique example of a developed country whose economy is dominated by export of natural resources. Thanks to its large petroleum reserves Norway has become one of the richest countries in the world. This thesis examines how the country has coped with its transformation and if it has avoided the so-called resource curse. It deals with the effects of the oil industry on the other sectors of the economy as well as on Norwegians' wellbeing. As the revenue from the petroleum production has grown, the state has implemented number of economic policies with the aim to utilize it in favour of the weakened industries and the society as a whole. So far, the oil industry has brought Norway prosperity thanks to sound governance and fitting policies. The question is whether the measures are sufficient to tackle both the decreasing production and prices of oil while maintaining the advantage the country has gained.